The Effect of Magnitude Mw and Distance Rrup on the Fragility Assessment of a Multistory RC Frame Due to Earthquake-Induced Structural Pounding - Maria G. Flenga; Maria J. Favvata (Buildings, 2023)
The effect of an intensity measure’s (IM’s) sufficiency property on the probabilistic assessment of reinforced concrete (RC) structures due to floor-to-floor structural pounding conditions is examined. In the first part of this investigation, efficiency and sufficiency properties of 23 scalar IMs are verified. Then, the magnitude Mw and the distance Rrup are examined as elements in a vector with an efficient scalar IM to evaluate whether they have any significant effect on the structural response. Subsequently, probabilistic seismic demand models (PSDMs) are developed using linear regression analyses based on a scalar IM and a vector-valued IM. Fragility curves are developed based on these PSDMs, and the influence of Mw and Rrup on the evaluation of the minimum required separation gap distance dg,min due to the pounding effect is examined. More than two hundred nonlinear time history analyses are performed based on the Cloud Analysis method. Seismic displacement demands that control of the global state of the structure, as well as the probability of structural pounding, are examined. The results of this research indicate that once Mw or Rrup is increased, fragility curves are shifted to greater values of IM, and the probability of the exceedance of a certain performance level is reduced. Also, the predictive power of Rrup seems to be greater than the one of Mw. On the other hand, it is revealed that Mw and Rrup induce variabilities in the demand solutions for adequate separation gap distance between the adjacent structures. Therefore, variation in Mw or Rrup may lead, in some cases, to unacceptable evaluations of the pounding effect in the capacity levels of structures.